2020
DOI: 10.3389/fcell.2020.569150
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-221/222 Mediates ADSC-Exosome-Induced Cardioprotection Against Ischemia/Reperfusion by Targeting PUMA and ETS-1

Abstract: Cardiovascular disease is a major health problem in industrialized and developing countries and is the leading cause of death and disability. Myocardial ischemia/reperfusion (I/R) causes cardiomyocyte damage such as apoptosis and hypertrophy. The purpose of this study was to investigate the effects of exosomes from adipose-derived stem cells (ADSC-Exo) on hearts from I/R mice and to explore the underlying mechanisms. ADSC-Exo significantly decreased I/R-induced cardiomyocyte apoptosis and hypertrophy, as detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 64 publications
0
41
0
Order By: Relevance
“…Moreover, we found that the miR-221/222-IRF2 axis is a functional mediator of the anti-inflammatory roles of propofol. However, several other molecular targets of miR-221/222 have been reported, such as Notch3 [ 27 ], CACNA1C and KCNJ5 [ 41 ], PUMA and ETS-1 [ 42 ], and genes involved in inflammatory response (ETS1/2, IRF2, BCL2L11, TOX, BMF, and CXCL12) [ 43 ], and whether these targets are involved in the anti-inflammatory roles of propofol in microglia remains an area of active study. Notably, miRNA-based therapies for disease treatments are under rapid clinical development [ 24 ]; targeting mir-221/222 may provide innovative practical therapeutics for patients with traumatic brain injury and ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that the miR-221/222-IRF2 axis is a functional mediator of the anti-inflammatory roles of propofol. However, several other molecular targets of miR-221/222 have been reported, such as Notch3 [ 27 ], CACNA1C and KCNJ5 [ 41 ], PUMA and ETS-1 [ 42 ], and genes involved in inflammatory response (ETS1/2, IRF2, BCL2L11, TOX, BMF, and CXCL12) [ 43 ], and whether these targets are involved in the anti-inflammatory roles of propofol in microglia remains an area of active study. Notably, miRNA-based therapies for disease treatments are under rapid clinical development [ 24 ]; targeting mir-221/222 may provide innovative practical therapeutics for patients with traumatic brain injury and ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-reperfusion injury is a hallmark of myocardial infarction, and it is a potent factor that increases exosome release in bone marrow-derived dendritic cells and macrophages [112]. In an inflammatory environment, dendritic cells downregulate the immune response by increasing the differentiation of CD4+ T cells into a Foxp3+ Treg antiinflammatory phenotype via exosome signaling [113,114]. Exosomal HP70 also released by dendritic cells stimulates the PI3K/mTOR axis regulating Treg and Th17 cell differentiation and attenuating ischemia-reperfusion injury [113].…”
Section: Ischemic Heart Disease and Acute Coronary Syndromementioning
confidence: 99%
“…For example, myelin oligodendrocytes count on exosomal secretion to promote axon transport and long axon maintenance in adjacent neurons (28). Adipose stem cell-derived exosomes inhibit ischemia-reperfusion injury of cardiomyocytes by targeting miR-221/miR-222/PUMA/ETS proto-oncogene 1 (ETS-1) pathway (29). Exosomal Hic-5 regulates the proliferation and apoptosis of osteosarcoma via Wnt/b-catenin signal pathway (30).…”
Section: Exosomes Mediate Intercellular Communicationmentioning
confidence: 99%